Perfil e estratificação de risco clínico frente a aplicabilidade de um instrumento a crianças de 0 a 5 anos hospitalizadas - Ferreira, Thalys Maynnard Costa (2024)
Introduction: the nursing process requires scientific knowledge to be executed, in addition to good clinical management, always starting from the human needs that the individual highlights, taking into account the individuality of the being as a carrier of a troubled health condition. The use of instruments, considered essential technologies for achieving quality and improving care in pediatrics, has been the subject of studies with their respective objects aimed at the growth and consolidation of nursing practices. Objective: to analyze the accuracy of an instrument for data collection and its correlation between risk stratification and clinical care profile in hospitalized children aged 0 to 5 years through the application of a validated tool. Method: methodological study, based on a quantitative-qualitative approach. The study included a sample of 220 children, aged 0 to 5 years, hospitalized in a pediatric clinic of three reference institutions for pediatric care in João Pessoa, and 27 nurses, working in the aforementioned pediatric clinics who met the inclusion criteria and exclusion. Operational stages of the study: 1) assessment of the instrument’s accuracy; 2) risk delineation and clinical profile; 3) applicability of the instrument by nurses and their perception of the process. The analysis of quantitative data was carried out using descriptive statistics, using the SPPSS software, and analytically, using Logistic Regression, under analysis mediated by the creation of a binary regression model. The qualitative data were subjected to lexicographic analysis, using the IRAMUTEQ software, by Classical Textual Statistics and Descending Hierarchical Classification (CHD), as well as the speeches were subjected to Content Analysis. The ethical and legal requirements of studies with human beings, as recommended in Resolution No. 466/12, were met, as well as the provisions of COFEN Resolution No. 564/2017, which concerns the Code of Ethics for Nursing Professionals. The project was submitted to the Research Ethics Committee of the Lauro Wanderley University Hospital, with protocol number 5,899,309. Results: the accuracy of the instrument was achieved based on the Intraclass Correlation Coefficient (ICC), with a value of 71.4% interjudge agreement, substantially achieved (0.969), classified as excellent, proving accuracy. A prevalent clinical profile was outlined, addressing syndromes established according to altered basic human needs, identifying numerical prevalence of respiratory, gastrointestinal, urinary and neurological syndromes. In the context of clinical risk, from the application of the logistic regression model, classification groups were created according to clinical risk scores: low risk (0-25), moderate risk (25-66) and high risk (66-150), faced with a sample with a low to moderate risk profile and, in turn, 12 variables that predicted high risk were highlighted, demonstrating measurement validity regarding clinical risk with a p-value <0.05, Nagelkerke coefficient (K²) 91.5% and satisfactory Odds Ratio, clarifying the effect and explanatory power of the model. Regarding the analysis of the interviewed nurses' speeches, two subbodies were generated, six classes and four subcategories, called: nursing history and the instrument for collecting pediatric data: guiding tool; nursing process and its implementation tools; pediatrics and its particularities: applicability of the instrument to children aged 0 to 5 years; computerization and improvements in care: care nuances. Conclusion: the instrument proved to be accurate and equipped with variables capable of, based on clinical analysis, contributing to the delineation of the clinical characteristics of hospitalized children aged 0 to 5 years and, also, stratifying the clinical risk based on the predictor variables of the high risk.